EFFECTS OF CORPORATE GOVERNANCE ON MANAGEMENT EFFICIENCY OF LITHUANIAN STATE-OWNED ENTERPRISES - Jurkonis, Liudas; Petrusauskaitė, Dovilė (Ekonomika, 2014)
Abstract. Management efficiency of state-owned enterprises (SOE) is being widely discussed not only in Lithuania, Central Eastern Europe, but also globally (mainly focusing on such countries as China, having state monopoly in most of the industries). Moreover, this topic is interesting to scholars both in the context of public governance reforms and a specific area of public administration. On the other hand, the topic of SOEs management is quite specific due to its duality: firstly, it is an area of public governance with an intensive intervention of the government, and secondly, SOEs are autonomous enterprises having dual – social (e.g., creation of work places, implementation of state-level projects, etc.) and economic (e.g., profitability, return on investment, etc.) – goals. Following the paradigms of (post) new public governance, principal agent theory, corporate governance guidelines established by such international organizations as the OECD, World Bank, International Monetary Fund and others, this paper is focusing on the management and performance of SOEs, trying to find an evidence of positive effects related to the implementation of corporate governance principles in Lithuanian SOEs. The paper seeks to identify those aspects of corporate governance which are the most relevant in terms of their potential effect on the management efficiency of Lithuanian SOEs.Key words: state-owned enterprises, corporate governance, principal agent theory, management efficiency